TEAM ASSISTED INDIVIDUALIZATION TO ENHANCE STUDENTS’ READING COMPREHENSION ON NARRATIVE TEXTS - An An Fitrianti N. (Institut Pendidikan Indonesia Garut, 2020)
This research aimed to examine the effectiveness of Team Assisted Individualization technique on students’ reading comprehension on narrative text. In addition to that this research was also aimed to find out the students’ responses on the use of that technique. To achieve those aims quantitative research with quasi-experimental design was chosen. In this research, there were 72 students participating in this research, consisting of experimental group and control group in one of junior high schools in Garut. The data in this research were collected from pre-test, post-test and closed questionnaire. Those data were then analyzed statistically using Mann Whitney test. As the result, Team Assisted Individualization is effective to improve students’ reading comprehension. It was seen from Zobserved3,487 > Zcritical1,96. Therefore, Ho was rejected and Ha was accepted. Moreover, the result of questionnaire analysis also revealed that students gave positive responses on the use of Team Assisted Individualization. In short, Team Assisted Individualization is effective to be used in teaching students’ reading comprehension on narrative texts.